Measuring Information Security Awareness Level of High School Students - Perkasa, Dimas Agung; Setiawan, Bambang (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
Information security awareness has become a crucial factor in the current advancement of information technology. Information security awareness is one of the key factors in avoiding crimes in the digital world today. Therefore, this research aims to measure the information security awareness level and provide recommendations to enhance the information security awareness of high school students. The research instrument utilized in this study is the Human Aspect Information Security Questionnaire (HAIS-Q) and focus area weighting was conducted using the Analytic Hierarchy Process (AHP) method. Data was collected through questionnaires distributed to 99 respondents, and the weighting was performed by two experts in the field of information security and one high school teacher. The results indicated a total awareness level of 86,38%, categorized as "Good", with the most vulnerable focus area being password management. Based on these findings, recommendations are provided in this research to enhance information security awareness.